Temporal Variations of 7Be and 210Pb Activity Concentrations in the Atmosphere and Aerosol Deposition Velocity in Shenzhen, South China - Guoqing Liu; Jiabao Wu; Yong Li; Lingling Su; Minxia Ding (Aerosol and Air Quality Research)
Abstract Naturally occurring beryllium-7 (7Be) and lead-210 (210Pb) serve as powerful tracers in atmospheric studies. In this study, 7Be and 210Pb were simultaneously measured in atmospheric aerosols and deposition samples for an entire year (from January to December 2017) in Shenzhen, South China. The activity concentrations of the airborne 7Be and 210Pb ranged from 0.33 to 9.42 mBq m−3 (averaging 3.23 mBq m−3) and from 0.59 to 4.72 mBq m−3 (averaging 1.58 mBq m−3), respectively, and were observed to be high during the winter but low during the summer. Moreover, the relatively high 210Pb concentration was probably due to the elevated level of radon in this region’s soil. The deposition fluxes of the 7Be and 210Pb were found to range from 0.25 to 3.04 Bq m−2 day−1 (averaging 1.57 Bq m−2 day−1) and from 0.34 to 1.31 Bq m−2 day−1 (averaging 0.73 Bq m−2 day−1), respectively. The temporal trends of these fluxes were largely influenced by rainfall and the origin and pathway of air masses, as well as by atmospheric circulation. Based on their concentrations in the aerosols and their deposition fluxes, the average deposition velocities of 7Be and 210Pb were calculated to be 0.83 and 0.62 cm s−1, respectively. The deposition velocities of both radionuclides correlated well with the amount of rainfall, indicating that precipitation plays a crucial role in removing 7Be and 210Pb from the air. The activity size distributions of these nuclides combined with the characteristic meteorological conditions in this region resulted in high deposition velocities during summer and low ones during winter.